Les âges de l’intelligence féminine dans les textes scientifiques et littéraires du XVIIIe siècle français : éléments d’une théorie androcentrique - Gargam, Adeline (Romanica Silesiana)
Women’s Intelligence Ages in Scientific and Literary Texts of the French 18th Century : Elements of an Androcentric Theory Women’s access to knowledge encountered the problem of legitimacy during the Enlightenment. According to 18th century doctors, invoking the so called natural features of women, this access was dependent on their ontogenesis. These scientific theories had a great impact on philosophical and literary works of the period. The examination of both discourses shows how they helped in creating the androcentric vision of women’s intellect, which is a world apart and subject to instabilities. Key words: theories about feminity, intellect, womb, interferences between scientific and literary texts, androcentrism.